Bacterial contamination of tomatoes sellers in eight traditional markets of Jember Regency, East Java, Indonesia - Laili, Nikmatul; Suswati, Enny; Abrori, Cholis; Mufida, Diana Chusna; Hermansyah, Bagus; Putri, Elvia Rahmi Marga (Universitas Gadjah Mada, 2024)
Purpose: Foodborne diseases are a significant threat to public health and is often associated with pathogenic microorganisms entering the body due to consuming contaminated food. One of the factors causing foodborne diseases was the contamination of pathogenic bacteria in vegetables consumed raw, one of which is tomatoes. This study was conducted to determine the correlation between traders' personal hygiene behavior and bacterial contamination of tomatoes in the traditional Jember Regency market. Methods: This study used analytical observational research with a cross-sectional research design, conducted in the Laboratory of Microbiology, Faculty of Medicine, University of Jember. The large sample size of this study was 40 traders. Personal hygiene behavior of traders was obtained from direct observation with observation sheets in eight selected traditional markets in Jember Regency. Results: Tomato samples were contaminated with bacteria with the highest bacterial colony >2.5 x 108 CFU/g and the lowest 4.6 x 105 CFU/g. The types of bacteria found in this study were Vibrio parahaemolyticus (15%), Shigella sp. (62.5%), Salmonella sp. (72.5%), Vibrio cholerae (82.5%), Escherichia coli (90%), and Staphylococcus aureus (92.5%). The bivariate test results showed no significant correlation between personal hygiene, sanitation, supporting facilities, and traders' characteristics with bacterial contamination of tomatoes sold in eight Jember traditional markets. Conclusion: This study concludes that there is no significant correlation between traders' personal hygiene behavior and bacterial contamination in tomatoes sold in eight traditional markets of Jember Regency. Consumers should wash tomatoes well or process them first before consumption.